(untitled) (REMUNOM, 2026)
This article, the result of studies and reflections on the reality of children aged 0 to 5 living in rural areas, has the following general objective: To analyze how the realization of the right to early childhood education (0 to 5 years) in/of rural areas occurs in the Cantuquiriguaçu Territory, specifically in the municipality of Pinhão, PR. The specific objectives are: To historically contextualize the constitution of early childhood education policies and Rural Education, highlighting the legal and regulatory frameworks and their effects on the recognition of rights; To map and characterize the Cantuquiriguaçu Territory; To identify the extent of early childhood education provision in the territory; To analyze the reality of the municipality of Pinhão. Characterized as qualitative documentary research, with a case study, it is organized into three movements: contextualization of rural early childhood education policies; territorial analysis of a specific reality in Paraná, the Cantuquiriguaçu Territory, comparing how the municipalities addressed, or not, rural early childhood education during the implementation of policies in the area; and an in-depth study of the only municipality in the territory that has a CMEI (Municipal Early Childhood Education Center) located in a rural area. This analysis strategy combines a normative review (Constitution, ECA, LDB, and Rural Education frameworks), reading of territorial and educational planning documents, and the use of secondary data and public statistics to characterize the population, school network, and provision (IBGE; Atlas Brasil; QEdu; guides and diagnoses cited in the text), culminating in a critical interpretation of inequalities and omissions in policy implementation.